Effect of fertigation on field-grown tomato (Lycopersicon esculentum) - Singandhupe, R B; Antony, Edna; Mohanty, S; Srivastava, R C (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during the winter season of 2003-2004 in field-grown tomato (Lycopersicon esculentum Miller. nom. cons.). Application of 31% and 69% N from 58 kg N/ha during initial crop-growth stages and flowering to reproductive stages, respectively, resulted 41 tonnes/ha total fruit yield (marketable and non-marketable) and saved 27.5% N compared to recommended dose of 8O kg N/ha, applied in 10 equal splits at 7-day intervals with 50% during vegetative and rest 50% during flowering to reproductive stage. The nitrogen recovery, agronomic efficiency and physiological efficiency was 38%, 286 kg fruit yield/kg applied N and 930 kg fruit yield/kg N uptake, respectively, in 58 kg N/ha dose. In other treatments where 23.5 to 27.3% N was applied during vegetative stages and rest 72.7 to 76.3% during flowering to reproductive stages resulted in 38.6-40.5 tonnes/ha fruit yield. In general, application of more quantity of N during reproductive stage enhanced the vegetative growth and produced less fruit yield.